2022
DOI: 10.5468/ogs.22190
|View full text |Cite
|
Sign up to set email alerts
|

Red cell alloimmunization in pregnancy: a study from a premier tertiary care centre of Western India

Abstract: The study was conducted to determine the frequency of alloimmunization to various blood group antibodies in pregnant women, and the risk of hemolytic disease in the fetus and newborn. MethodsAll antenatal women, irrespective of the period of gestation or obstetric history, were included, whereas those taking anti-D immune-prophylaxis or with a history of blood transfusion were excluded. Antibody screening and identification were performed using a Bio-Rad ID microtyping system. ResultsOf 2,084 antenatal females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Other blood group antibodies that the screening cell showed positive but reaction pattern is not indicative any in the antigram (most probably low-frequency antigen of unknown specificity) recorded 2 (2.7%) while 1 (1.4%) of the screening cell shows positive while the specificity showed negative. This findings is in agreement with previous reports of Gothwal and colleagues reported that (3.119%) of pregnant women were alloimmunized with specificity of anti-M (9.23%), anti-c (3.076%), anti-E (1.538%), anti-e (1.538%), anti-Lewis (a) (1.538%), unspecified antibodies (1.538%), multiple antibodies anti-D and anti-C (3.076%), anti-e and anti-c (1.538%), and anti-D and anti-G (1.538%) in tertiary care centre of Western India [11] and that of Karim and colleagues in Pakistan reported the frequency of maternal alloimmunization among pregnant women was 1.8% of with specificity of non-anti-D (1.6%), anti-M (15%), anti-Lewis(a) (15%), anti-c (5%), anti-E (5%), anti-e (5%), anti-Lewis(b) (5%) and nonspecific antibodies (30%) and the prevalence of anti-D 2.9% in D negative blood type [12] as well as the report of [13] Ugandan who reported that 2•2% of pregnant women were alloimmunized to RBC antigens with specificity including anti-S, 12; anti-M, 11; anti-Lea, 6; anti-D, 4 and 1 each of anti-K, anti-Fyb, anti-Jka, anti-Lua and anti-Kpa. [14] in isreal also reported that 5.8% of the pregnant women had antibody with specificity of anti-E (23%), anti-K (16%), and anti-c (10.8%) and multiple alloantibodies were observed in 15% of women and severe HDFN developed in 6.8% of these pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…Other blood group antibodies that the screening cell showed positive but reaction pattern is not indicative any in the antigram (most probably low-frequency antigen of unknown specificity) recorded 2 (2.7%) while 1 (1.4%) of the screening cell shows positive while the specificity showed negative. This findings is in agreement with previous reports of Gothwal and colleagues reported that (3.119%) of pregnant women were alloimmunized with specificity of anti-M (9.23%), anti-c (3.076%), anti-E (1.538%), anti-e (1.538%), anti-Lewis (a) (1.538%), unspecified antibodies (1.538%), multiple antibodies anti-D and anti-C (3.076%), anti-e and anti-c (1.538%), and anti-D and anti-G (1.538%) in tertiary care centre of Western India [11] and that of Karim and colleagues in Pakistan reported the frequency of maternal alloimmunization among pregnant women was 1.8% of with specificity of non-anti-D (1.6%), anti-M (15%), anti-Lewis(a) (15%), anti-c (5%), anti-E (5%), anti-e (5%), anti-Lewis(b) (5%) and nonspecific antibodies (30%) and the prevalence of anti-D 2.9% in D negative blood type [12] as well as the report of [13] Ugandan who reported that 2•2% of pregnant women were alloimmunized to RBC antigens with specificity including anti-S, 12; anti-M, 11; anti-Lea, 6; anti-D, 4 and 1 each of anti-K, anti-Fyb, anti-Jka, anti-Lua and anti-Kpa. [14] in isreal also reported that 5.8% of the pregnant women had antibody with specificity of anti-E (23%), anti-K (16%), and anti-c (10.8%) and multiple alloantibodies were observed in 15% of women and severe HDFN developed in 6.8% of these pregnancies.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 However, some other studies by Gothwal et al and Suresh et al suggest that routine antibody screen should restrict to patients with bad obstetric history. 19,20 Though the screening done on a pregnant patient at first visit is a matter of debate in the country, the test done at 28 weeks or thereafter should not be of much argument as the same IAT test is essential component of compatibility test for red cell transfusions. PRBC transfusion is not an uncommon practice in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
“…1 Red blood cell alloimmunization among pregnant women range from 0.4% to 2.7% globally. [2][3][4] The most clinically relevant blood group antigen present on the surface of red blood cells is still the ABO and Rhesus (Rh) blood group system. 5 Rh alloimmunization happens when the immune system of the mother becomes sensitive to the RhD erythrocyte surface antigens, but it also refers to sensitization to other Rh antigens, including c, C, E and e. 6 Alloimmunization, a process that produces a template for the production of antibodies as well as small amounts of antibodies against the RhD antigen, can occur in a mother who is D-negative when fetal D-positive cells are present in her circulation.…”
Section: Introductionmentioning
confidence: 99%